2017
DOI: 10.1038/srep41873
|View full text |Cite
|
Sign up to set email alerts
|

The interrelated effect of sleep and learning in dogs (Canis familiaris); an EEG and behavioural study

Abstract: The active role of sleep in memory consolidation is still debated, and due to a large between-species variation, the investigation of a wide range of different animal species (besides humans and laboratory rodents) is necessary. The present study applied a fully non-invasive methodology to study sleep and memory in domestic dogs, a species proven to be a good model of human awake behaviours. Polysomnography recordings performed following a command learning task provide evidence that learning has an effect on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 37 publications
2
79
3
Order By: Relevance
“…The data set that we used was from Kis et al . 4 from an experiment specifically designed to test the contributions of sleep to memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…The data set that we used was from Kis et al . 4 from an experiment specifically designed to test the contributions of sleep to memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, pet dogs that had owners who tended to play more with them during the manipulation phase of a task committed more errors when retested in a memory task (Sümegi et al, 2014). These results might be used to suggest that the valence of the arousal rather than the level of arousal per se affects memory; however, Kis et al (2017) found no long-term effect of the play session on memory in a learning task despite finding decreased performance after a bout of play. This result suggests that the emotional arousal following play may not interfere with memory consolidation so much but instead might have more of an effect on other processes relevant to performance, such as attention.…”
Section: Arousal Performance and Learning Effectsmentioning
confidence: 80%
“…The sleep macrostructure of dogs is composed of the stages of awakeness, drowsiness, non-REM and REM [24,39]. Beta activity (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) is the dominant characteristic of dogs' awake state. The drowsiness stage is a transition between waking and sleep (characteristic of carnivore or insectivore species where the distinction between the awake and sleeping states is not clear [8]), and has been observed in dogs as well, with the highest power in the alpha band.…”
Section: Introductionmentioning
confidence: 99%